Labor Flexibility of the Working Population: a Spatial Analysis in Mexico, 2005 and 2014 - Román Sánchez, Yuliana Gabriela; Ovando Aldana, Wendy (Sociedad y Economía, 2016)
This article aims to analyze regional differences in working conditions of the workingpopulation in Mexico. To do this, an index of labor flexibility is estimated considering theyears 2005 and 2014. The study is based on the Labor Market Segmentation Theory. Theresults show the existence of regional differences in Mexican territory which enable toidentify a spatial pattern that is displayed in 2005 and 2014: The northern states of Mexicoexhibit a low flexibility index, those of center of Mexico show an average index, and thesouthern states display a high flexibility index. This confirms that in fact, labor markets inMexico hold flexibility as transcendental particularity, phenomenon observed before thelabor reform and today.